Estudio y diseño de la red de agua potable, de los sistemas de alcantarillado sanitario y pluvial de la lotización 23 de Diciembre de la parroquia Bellavista, cantón Santa Rosa, provincia de El Oro. - Segarra Blacio, Michael Mauricio (2015)
This research is of great convenience for our province because it brings with curves deterioration which will allow us to reduce the costs of maintenance and rehabilitation of wagons asphalt of the Province of El Oro, which helps to know what kind of maintenance can give you to the road. Through this work GPAO beneficiaries are the inhabitants of the cantons where information which can give them safer from all parts of the upper part of the province of El Oro trip was obtained. The models will be used by the traffic management system plan of the province whose optimization is based on the performance of future resource needs in order to achieve the desired levels of condition. It helps in the analysis and interpretation of deterioration that occurs on asphalt roads in the province which will allow us to give a longer shelf life. To carry out this research counted on the experience of Dr. Luis Amador which develops this research, he had the support of a public institution such as the Provincial Autonomous Government of El Oro who provided with information necessary for conducting the investigation.